2023
DOI: 10.1136/svn-2022-001765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy with combined stent retriever and contact aspiration versus stent retriever alone for acute large vessel occlusion: data from ANGEL-ACT registry

Abstract: Background and purposeAn analysis of the ASTER 2 trial revealed similar final recanalisation levels and clinical outcomes in acute large vessel occlusion (LVO) stroke between stent retrieval (SR) alone as a first-line mechanical thrombectomy (MT) technique (SR alone first-line) and concomitant use of contact aspiration (CA) plus SR as a first-line MT technique (SR+CA first-line). The purpose of the present study was to compare the safety and efficacy of SR+CA first-line with those of SR alone first-line for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
(74 reference statements)
2
13
0
Order By: Relevance
“…The aspiration catheter was not widely used throughout China between 2017 and 2019; interventionists preferred to use the SR alone for the first-line EVT procedure during this study period. 43 Limitations of our study include the lack of core lab evaluation for TICI grade scaling after EVT. Moreover, precise information concerning the CA and SR devices (manufacturer, length, diameters) were not included in our analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The aspiration catheter was not widely used throughout China between 2017 and 2019; interventionists preferred to use the SR alone for the first-line EVT procedure during this study period. 43 Limitations of our study include the lack of core lab evaluation for TICI grade scaling after EVT. Moreover, precise information concerning the CA and SR devices (manufacturer, length, diameters) were not included in our analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The aspiration catheter was not widely used throughout China between 2017 and 2019; interventionists preferred to use the SR alone for the first-line EVT procedure during this study period. 43…”
Section: Discussionmentioning
confidence: 99%
“…4 Similar results were reported when CoT and standalone SR were compared although the reported FPE rates were controversial. 5,6 Indeed, while Okuda et al 11 observed higher FPE rates with CoT compared with SR, Huo et al 12 showed that a higher number of passes and longer procedure times were associated with the use of CoT compared with SR alone. In our subgroup analysis, we did not find any difference between the 2 techniques in terms of FPE, but, interestingly, we showed significantly better results of CoT over SR alone in ICA terminus±M1-MCA occlusions considering eTICI ≥2b50 and eTICI ≥2c at the end of the first-line strategy.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were reported about intraprocedural complications when the 3 techniques were compared. 4,5,11,12 ICA Terminus: A Location for New Devices and Techniques?…”
Section: Cot Versus Ca and Srmentioning
confidence: 99%
See 1 more Smart Citation